Matter-Robotic Calibration for Bioshotcrete - Maite Bravo; Stephanie Chaltiel; Wilfredo Carazas (Temes de Disseny)
Construction techniques associated with traditional raw earth architecture are characterised by laborious manual tasks in which each clay mix is deposited in layers over a light formwork, such as with the wattle and daub technique. More sustainable solutions also exist for the use of concrete, including shotcrete or sprayed concrete over light formwork composed of fabrics, inflatables or metal meshes. This research explores robotic techniques for the digital fabrication of monolithic earthen shells, with the objective of reformulating the use of clay as a sustainable material to reduce laborious tasks, minimize the use of formwork, and to implement robotic fabrication processes. This unique technique is called “bioshotcrete” and is characterised by an innovative fabrication process of sequential robotic spraying deposition of different natural raw clay mixes over a temporary light formwork. Two case studies are described and analysed featuring two distinctive techniques: clay mixes sprayed with a robotic arm and with a drone. Details are highlighted, and key considerations are identified, in terms of subtle adjustments for the material formulation and application sequences, robotic tooling strategies, and customised robotic actions. This series of experiments was formulated as an ongoing experiment to address challenges related to limitations of reaching distances and lightness of machines to bring on site, and to explore newfound possibilities for aerial deposition techniques using drones. Variations related to Tool/Matter performance (spray velocity and surface adhesion) were explored at each clay mixture iteration. Additional improvements were identified by recent physical tests, such as using the drafts created by the drone helixes to help the drying process at each layer, and additional conclusions establish how this technique is not only shaping new design and digital fabrication processes but envisioning possible future applications and offering new scenarios for sustainable large-scale earthen envelopes.